2014
DOI: 10.1016/j.jmb.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between Cytoplasmic Retroviral Gag Concentration and Gag–Membrane Association

Abstract: The early events in the retrovirus assembly pathway, particularly the timing and nature of Gag translocation from the site of protein translation to the inner leaflet of the plasma membrane, are poorly understood. We have investigated the interrelationship between cytoplasmic Gag concentration and plasma membrane association using complementary live-cell biophysical fluorescence techniques in real-time with both the human T-cell leukemia virus type 1 (HTLV-1) and human immunodeficiency virus type 1 (HIV-1) Gag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 72 publications
8
38
0
Order By: Relevance
“…5B), indicating that the majority of HIV/HIV-N Gag was unable to translocate to the PM. This agrees well with previous findings that indicate HIV-1 WT Gag-Gag interactions must occur before efficient Gag translocation to the PM (34).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…5B), indicating that the majority of HIV/HIV-N Gag was unable to translocate to the PM. This agrees well with previous findings that indicate HIV-1 WT Gag-Gag interactions must occur before efficient Gag translocation to the PM (34).…”
supporting
confidence: 93%
“…HTLV-1 and HIV-1 Gag proteins have markedly different Gag-Gag interactions and PM trafficking phenotypes based on previous studies (33,34). While HIV-1 Gag-Gag interactions occur in the cytoplasm, HTLV-1 Gag-Gag interactions initiate at the PM.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Gag multimerization is a critical component of the ability of Gag to bind stably to the PM. RSV MA and HIV MA with and without GFP are not localized to the PM (18,19,(58)(59)(60)(61)(62) The plateaus correspond to equilibrium responses at given protein concentrations. Gag remained bound to the membrane after the buffer rinse, while MA was almost completely removed.…”
Section: Resultsmentioning
confidence: 99%
“…Finally we applied our technique to study the membrane interactions of the matrix domain of human T-cell leukemia virus type 1 (HTLV-1) Gag. We previously observed that the Gag polyprotein and matrix (MA), its membrane-binding domain, of HTLV-1 interact with the plasma membrane at low cytoplasmic concentrations, which is in stark contrast with the corresponding proteins of the human immunodeficiency virus type 1 (HIV-1) (11)(12)(13). Here we expand our investigation of HTLV-1 virus assembly by characterizing the membrane binding curve for the MA domain of HTLV-1 Gag and the lipid-specificity of the interaction.…”
Section: Introductionmentioning
confidence: 99%